Basic Laboratory Management Training for Institutions - Srinatalia Silaen (EQUATOR SINAR AKADEMIA, 2023)
The objective of Basic Laboratory Training is to increase the competency of laboratory personnel in laboratory management in accordance with the needs and developments that occur in society, increase the ability of laboratory personnel to carry out their duties and career advancement, improve basic laboratory management skills. The method used in this activity is in the form of practice in the field and training. Therefore it is necessary to hold trainings, workshops and outreach to teachers, lecturers, researchers, librarians, laboratory assistants, technicians, educators so that their soft skills develop and improve. One of these trainings is basic laboratory socialization training for tertiary institutions, especially in the fields of chemistry, physics, biology, language and computers with the concept of independent learning while increasing the ability to become proficient in the laboratory world later. The background of the problem in this research is developing accuracy and understanding of the world of laboratory assistants through training workshops and socialization of independent learning at the tertiary level. Based on the formulation of the problem above, the purpose of this service is to develop the concept of independent learning at the tertiary level through training workshops and socialization of independent learning for students and lecturers to run better. Theoretical benefits in increasing the role of higher education laboratories in overcoming current problems in society, improving laboratory quality, increasing the ability of laboratory services to support the Tridharma of higher education.